2017
DOI: 10.1007/s11356-017-0956-4
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and research of microcystins and environmental factors in a typical artificial freshwater aquaculture pond

Abstract: Freshwater aquaculture ponds are important artificially regulated aquatic ecosystems which provide a large number of freshwater fish products in China. The cyanobacteria bloom and microcystin (MC) pollution caused by anthropogenic eutrophication have attracted much attention due to their toxic effects. To provide an insight into the cyanobacterial problem in the ponds, the environmental parameters and MCs of a typical artificial pond in the Yangtze River Delta region of China were monitored and studied from Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 67 publications
2
22
0
Order By: Relevance
“…The water quality factors that had strong driving effects towards the development of both phytoplankton and zooplankton communities was pH, which is consistent with the conclusions obtained in plankton‐based studies by Reynolds (2006) and Pinilla (2006). Phytoplankton communities are affected by WT to a greater extent, as phytoplankton growth and reproduction requires higher WT (Alam et al, 2001; Descy et al, 2016; Hu et al, 2018), whereas zooplankton communities are affected by Cond to a greater extent, which is consistent with the conclusions of the study on zooplankton by Walker and Pan (2006). The main chemical factors of water quality driving the development of phytoplankton communities were BOD, as appropriate levels of BOD can promote rapid phytoplankton reproduction (Hou, Song, Liu, Xiao, & Liu, 2004; Salomoni, Rocha, Callegaro, & Lobo, 2006; Zhu, Wang, Chen, Shen, & Deng, 2018).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The water quality factors that had strong driving effects towards the development of both phytoplankton and zooplankton communities was pH, which is consistent with the conclusions obtained in plankton‐based studies by Reynolds (2006) and Pinilla (2006). Phytoplankton communities are affected by WT to a greater extent, as phytoplankton growth and reproduction requires higher WT (Alam et al, 2001; Descy et al, 2016; Hu et al, 2018), whereas zooplankton communities are affected by Cond to a greater extent, which is consistent with the conclusions of the study on zooplankton by Walker and Pan (2006). The main chemical factors of water quality driving the development of phytoplankton communities were BOD, as appropriate levels of BOD can promote rapid phytoplankton reproduction (Hou, Song, Liu, Xiao, & Liu, 2004; Salomoni, Rocha, Callegaro, & Lobo, 2006; Zhu, Wang, Chen, Shen, & Deng, 2018).…”
Section: Resultssupporting
confidence: 72%
“…In terms of phytoplankton growth habits, their reproduction depends on an appropriate WT (Sinden & Sinang, 2016). WT is the most important physical driving factor for controlling algae resuscitation, reproduction and outbreaks (Figueredo & Giani, 2009; Hu et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…MCs pose a threat to human health in many ways, such as oral, dermal and inhalation pathways, and exposure may occur during recreation depending on the types of activities undertaken in the water[ 4 , 5 ]. Freshwater aquaculture ponds are important artificially regulated aquatic ecosystems that provide a large number of freshwater fish products in China[ 6 ]. Moreover, China’s freshwater aquaculture area and production stands first in the world[ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, China’s freshwater aquaculture area and production stands first in the world[ 7 ]. Studies have shown that MCs can accumulate in a variety of aquatic organisms, such as zooplankton, bivalves, crustaceans, fish, and aquatic vertebrates[ 6 ]. It may exert a potential toxic hazard to humans after the consumption of MC-contaminated aquatic products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation